Kisebbségi magyarok az első Csehszlovák Köztársaságban - Kugler, József (Közép-Európai Közlemények, 2011)
As a result of the Trianon Peace Treaty, more than one million Hungarians were forced to choose the status of ethnic minority of Czechoslovakia, as it was relected by the national statistics of Hungary. This major group included Hungarians who lived also in the recent territory of Slovakia and Ukraine. During the 1920s and the 1930s, the national governments of Czechoslovakia were endeavouring to set the framework for parliamentary democracy and to re)organise the national economy (favouring the Czech areas), while decisions over key issues related to those were increas)ingly centralized at national governmental level. Such policies raised negative and also positive aspects of daily practices of the Hungarian ethnic minority. While the economic prosperity im)proved the quality of life of small holders, Hungarian)speaking intellectuals faced with major diffi)culties in the framework of the new public administration.